Factors that hinder community participation in developing and implementing comprehensive council health plans in Manyoni District, Tanzania - Emmanuel G. Kilewo (Global Health Action, 2015)
Background: Decentralization of public health planning is proposed to facilitate public participation in health issues. Health Sector Reform in Tanzania places emphasis on the participation of lower level health facilities and community in health planning process. Despite availability of policies, guidelines, and community representative organs, actual implementation of decentralization strategies is poorly achieved. This study intended to find out factors that hinder community participation in developing and implementing Comprehensive Council Health Plan (CCHP). Materials and methods: A qualitative approach was conducted in this study with key informants from Health Facility Governing Committees (HFGC), Council Health Service Board (CHSB), and Council Health Management Team (CHMT). Data were collected using in-depth interviews. Data generated were analyzed for themes and patterns. Results: Factors that hindered community participation included lack of awareness on the CCHP among HFGC members, poor communication and information sharing between CHMT and HFGC, unstipulated roles and responsibilities of HFGC, lack of management capacity among HFGC members, and lack of financial resources for implementing HFGC activities. Conclusions: The identified challenges call for policy makers to revisit the decentralization by devolution policy by ensuring that local governance structures have adequate resources as well as autonomy to participate in planning and managing CCHP in general and health facility plans in particular.